If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) + -2(x + -4) = 12 Reorder the terms: 3(5 + x) + -2(x + -4) = 12 (5 * 3 + x * 3) + -2(x + -4) = 12 (15 + 3x) + -2(x + -4) = 12 Reorder the terms: 15 + 3x + -2(-4 + x) = 12 15 + 3x + (-4 * -2 + x * -2) = 12 15 + 3x + (8 + -2x) = 12 Reorder the terms: 15 + 8 + 3x + -2x = 12 Combine like terms: 15 + 8 = 23 23 + 3x + -2x = 12 Combine like terms: 3x + -2x = 1x 23 + 1x = 12 Solving 23 + 1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 1x = 12 + -23 Combine like terms: 23 + -23 = 0 0 + 1x = 12 + -23 1x = 12 + -23 Combine like terms: 12 + -23 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| -13+2x=-52+7x | | 4t-3=6+3t | | Y=4.2+3.6*4 | | 3(6x+5)=33 | | 0=7x^2-36x | | 2x=7x+2 | | X-12=89 | | 41x-17y-9=0 | | 100x^3-x^5=0 | | 12=-6c-4 | | 3x-27/3x= | | -32,424/-84 | | 2x-5(x-5)=-3+4x+14 | | -(x)(x+0)(x-5)=0 | | 4+2=5x+1 | | 5(m-3)=24 | | (x-5)(x+0)(x+7)=0 | | X/Y=-4/5 | | (15/10)^(1/4)-1 | | 8x+1=31 | | (b+16)(b-18)=0 | | 9-4(2x-1)-3x+2= | | 3x^4-21x^3+24x^2+23x-34=0 | | 20(7u-8v+3w)= | | 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 |